2013
DOI: 10.1016/j.jinorgbio.2013.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Intercalative interaction of asymmetric copper(II) complex with DNA: Experimental, molecular docking, molecular dynamics and TDDFT studies

Abstract: The intercalative interactions of small molecules with DNA are important in a variety of biological processes including mutagenesis, carcinogenesis, and chemotherapy. A comprehensive research protocol including experiments and calculations was employed to investigate the intercalative interaction between metallointercalator copper(II) complex and DNA. The intercalative binding mode has been validated by UV spectra, fluorescence spectra, CD spectra and viscosity measurements. The classical molecular dynamics si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Intercalation occurs when the small molecules intercalate within the nucleic acid base pairs [2,3]. Many small molecules of biological importance are known to interact with DNA through non-covalent interactions [4][5][6]. These small molecules are known to interact with DNA by a specific binding mode.…”
Section: Introductionmentioning
confidence: 99%
“…Intercalation occurs when the small molecules intercalate within the nucleic acid base pairs [2,3]. Many small molecules of biological importance are known to interact with DNA through non-covalent interactions [4][5][6]. These small molecules are known to interact with DNA by a specific binding mode.…”
Section: Introductionmentioning
confidence: 99%
“…Further computational studies modeling the drug-DNA interactions have suggested the atomic mechanism by which complexes can interact with either the grooves of the DNA or via intercalation between base pairs, and these studies have suggested information about the thermodynamic and energetic properties ( 2 , 40 ). Several groups have applied molecular dynamics (MD), quantum mechanics (QM) and hybrid methodologies (QM/MM) to models of copper complexes binding with DNA ( 41 45 ). The complex Cu[1,10-phenthroline] 2+ with multiple functional groups and a serinol link between the ligands have been studied by Magistrato and co-workers using MD and QM and the simulations and energetic analyses suggest that these complexes bind to the DNA in the minor groove with a partial intercalation between base pairs ( 43 ) with related calculations using QM methodologies yielding similar results ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) calculations provide powerful tools for studying the structural, interaction potentials and dynamic characterization of biological macromolecules involving nuclear acid [27]. For example, binding properties of the reversible diamidines with DNA by using MD simulations were investigated that influence of the central heterocycle is greater than that of tail part for reversible amidines binding affinity to DNA [28].…”
mentioning
confidence: 99%